Synergy of Collaborative Governance and Penta Helix in Community-Based Waste Management: Evidence from the Pesan Pede Program in Celuk Village - I Gusti Ayu Rima Cahyaniti; Ida Bagus Teddy Prianthara (Jurnal Locus Penelitian dan Pengabdian, 2026)
This research examines the synergy between collaborative governance and the penta helix approach in community-based waste management through the Pesan Pede Program in Celuk Village, Sukawati District, Gianyar Regency, Bali. Waste management remains a complex public issue, often constrained by top-down approaches that fail to fully engage communities. This research employs a qualitative descriptive method, with data collected through in-depth interviews, field observations, and documentation. The data were analyzed using an interactive model involving data reduction, data display, and conclusion drawing. The findings reveal that collaborative governance operates effectively through continuous dialogue, trust-building, shared commitment, and mutual understanding among stakeholders. The penta helix framework demonstrates that the community acts as the core actor, while the government serves as a facilitator, academics contribute knowledge, the private sector supports economic activities, and the media enhances public awareness and legitimacy. The integration of these two approaches produces a sustainable, community-driven waste management system rooted in local socio-cultural values. The study highlights that effective waste management is not solely determined by formal policies or technological solutions, but by the ability to integrate collaborative processes with local cultural dynamics. This research proposes an embedded collaborative governance model based on a community-driven penta helix, offering both theoretical and practical contributions to public administration studies.